2010
DOI: 10.1097/aog.0b013e3181e904e5
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes in Women With Thyroid Peroxidase Antibodies

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 18 publications
2
70
1
6
Order By: Relevance
“…Our findings were similar to that of Abbassi-Ghanavati and associates who did not find any increased risk for preterm birth in TPO positive women compared with the risk in euthyroid women with TPOAb -ve. 10 Our results of preeclampsia and preterm labour may be due to very less numbers. It could have been overcome if sample size becomes larger.…”
Section: Discussionmentioning
confidence: 78%
“…Our findings were similar to that of Abbassi-Ghanavati and associates who did not find any increased risk for preterm birth in TPO positive women compared with the risk in euthyroid women with TPOAb -ve. 10 Our results of preeclampsia and preterm labour may be due to very less numbers. It could have been overcome if sample size becomes larger.…”
Section: Discussionmentioning
confidence: 78%
“…Multiple observational studies [63,64,65] and 2 meta-analyses [66,67] have confirmed a 2-4 fold risk of miscarriage among euthyroid TPO antibody-positive women, compared to euthyroid TPO antibody-negative women. Some studies [68,69] but not all [70,71], have also found associations between thyroid autoimmunity and increased rates of recurrent miscarriage.…”
Section: Thyroid Auto-immunitymentioning
confidence: 99%
“…Serum TSH level [3 mu/l and normal range free T4 were considered as subclinical hypothyroidism [11]. Normal serum TSH level and free T4 \0.86 ng/dl were considered as maternal hypothyroxinemia [22,23].…”
Section: Methodsmentioning
confidence: 99%
“…Although many types of antithyroid antibodies have been described, the most common is the group of antibodies directed against various parts of the thyroid peroxidase molecule [24][25][26]. Most pregnant women with abnormally elevated serum levels of thyroid peroxidase antibodies are clinically and biochemically euthyroid, but they may be at increased risk of spontaneous abortion, and preterm delivery and other pregnancy complications [11,27].…”
Section: Observationmentioning
confidence: 99%
See 1 more Smart Citation